Diachronic changes the Nicaraguan sign language classifier system: Semantic and phonological factors - Davis Jeffery; Brentari Diane (Open Linguistics)
This article presents an exploration of the usage and distribution of the 1-handshape classifier (Cl-1) and the 2-handshape classifier (Cl-2), both diachronically and synchronically, tracking classifier development in a detailed dataset of Nicaraguan individual homesigners and two groups of Nicaraguan Sign Language signers. Both phonological and semantic dimensions are analyzed in service of discerning what factors impact the choice and phonological production of the relevant classifiers. Phonologically we find that the distribution of Cl-1 and Cl-2 is quite different than would be expected were articulatory complexity the main motivating factor. We suggest also that this dataset is a microcosm of the system as a whole, and patterns of 1-handed and 2-handed signs vary across groups. Semantically, we find that (1) classifier use is more semantically restricted among individual homesigners. (2) As classifiers become more semantically frequent and flexible in the earliest cohort of Nicaraguan signers, constraints on production emerge. (3) Vertical transmission of those classifiers and constraints leads to more flexible usage in subsequent cohorts.